NCOA3 identified as a new candidate to explain autosomal dominant progressive hearing loss. (17th December 2020) - Salazar-Silva, R; Dantas, Vitor Lima Goes; Alves, Leandro Ucela; Batissoco, Ana Carla; Oiticica, Jeanne; Lawrence, Elizabeth A; Kawafi, Abdelwahab; Yang, Yushi; Nicastro, Fernanda Stávale; Novaes, Beatriz Caiuby; Hammond, Chrissy; Kague, Erika; et al.
Abstract: Hearing loss is a frequent sensory impairment in humans and genetic factors account for an elevated fraction of the cases. We have investigated a large family of five generations, with 15 reported individuals presenting non-syndromic, sensorineural, bilateral and progressive hearing loss, segregating as an autosomal dominant condition. Linkage analysis, using SNP-array and selected microsatellites, identified a region of near 13 cM in chromosome 20 as the best candidate to harbour the causative mutation. After exome sequencing and filtering of variants, only one predicted deleterious variant in the NCOA3 gene (NM_181659, c.2810C > G; p.Ser937Cys) fit in with our linkage data. RT-PCR, immunostaining and in situ hybridization showed expression of ncoa3 in the inner ear of mice and zebrafish. We generated a stable homozygous zebrafish mutant line using the CRISPR/Cas9 system. ncoa3−/− did not display any major morphological abnormalities in the ear, however, anterior macular hair cells showed altered orientation. Surprisingly, chondrocytes forming the ear cartilage showed abnormal behaviour in ncoa3−/−, detaching from their location, invading the ear canal and blocking the cristae. Adult mutants displayed accumulation of denser material wrapping the otoliths of ncoa3−/− and increased bone mineral density. Altered zebrafish swimming behaviour corroborates a potential role of ncoa3 in hearing loss. In conclusion, we identified a potential candidate gene to explain hereditary hearing loss, and our functional analyses suggest subtle and abnormal skeletal behaviour as mechanisms involved in the pathogenesis of progressive sensory function impairment.